Pemanfaatan Data Satelit Himawari-8 Dalam Analisa Kejadian Hujan Lebat Di Jombang Tanggal 1-2 Februari 2021 - Sulistiyono, Wahyu; Tuna, Miranda Sahfira; Ramadhan, Shandy Alhaq (Universitas Mandiri, 2024)
The occurrence of a flood in the Jombang area on February 2, 2021, caused damage to 38 houses and public facilities. Flood events are caused by high-intensity rain produced by cumulonimbus clouds. Analysis of the development of convective clouds is needed to see the microphysics stage of rain-producing clouds. In this study, the analysis of convective clouds and atmospheric conditions was carried out using the Himawari-8 Satellite. Processing is carried out using the RGB Day Convective Storm, 24H-Microphysics, Airmass, and Cloud Convective Overlay methods. Based on the results of the study, it is known that the convective cloud microphysics phase occurs in 2 phases with different times on the 1st and 2. In the cloud top temperature analysis, during the Cb cloud development phase, the cloud top temperature is in the value range of -20 to -60 0C. Based on Airmass imagery, it is observed that convective cloud clusters originate from the waters of the Java Sea and the South Sea. The peak phase of cloud formation occurs at 12.00 UTC on February 1 and 2. Convective cloud formation increases when the updraft value strengthens and the intensity of cloud thickness increases. Meanwhile, the decay phase is marked by a higher downdraft value and a decrease in cloud distribution based on Day Convective Storm and 24H-Microphysics images.